Mechanical Effects of Solid Water on the Particle Skeleton of Soil: Mechanism Analysis - Xiaomeng Duan (Geofluids)
It is generally accepted that the adsorbed water layer on the surface of the mineral particle has significant effects on the mechanical properties of soils. By defining the concepts of “solid water” and “particle skeleton” after a brief review on adsorbed water, therefore, the mechanical mechanism about how solid water affects the deformation and strength of particle skeleton is theoretically clarified, which could be the physical basis of the reasonability of two assumptive conditions for effective stress equation. Considering solid water as a two-dimensional liquid with appreciable normal strength and lubricity, if soil particles are always wrapped by solid-water layer, the only mechanical effect due to water pressure is to compress particles; while if the interparticle solid water could be extruded undergoing enough force with suitable confinement, the mechanical effects due to increasing water pressure are not only to compress particles more but also to enhance interparticle friction because the indirect interparticle contact could be changed into direct contact to consequently alter the interparticle friction. Because solid water is not likely to be extruded by pressure alone, if the particle compression is negligible relative to the soil-mass compression, two assumptive conditions for effective stress equation are reasonable. Moreover, a simple monitoring test on water content is conducted to certify that the solid-water layer should always exist in soils under ambient conditions, so the ordinarily oven-dried soil samples used in conventional geotechnical tests carried out under ambient conditions could be just “nominally dry” samples with the effects due to solid water.